CSF Advisers Sdn Bhd / Nabila Shazlin Izwanie Mohd Naim - Mohd Naim, Nabila Shazlin Izwanie (Universiti Teknologi MARA, Perlis, 2023)
The duration of my industrial training requirement was 6-month at CSF Advisers Sdn. Bhd. And along with the time as well, I gained a lot of experience and memorable moment with everyone in my department as I am the youngest among my colleague. Before I started my industrial training at CSF Advisers Sdn Bhd, I am preparing my resume and other documents in order for me to send to companies that I have the thought in order for me to do my industrial training which will help me to get the position in the company. CSF Advisers Sdn. Bhd. is a telecommunication company that is known as Data centre. CSF Advisers Sdn. Bhd. is located at Cyberjaya, Selangor and the reason on why I choose this company because is the reason I chose is a very strategic location for me industrial training and I have facilities to go to work compared to other locations. In CSF Advisers Sdn. Bhd., I was assigned to be in the Human Resource Department which is same with my major course during study. In this department, they managed about event, medical claim, recruitments and also payroll. I studied the payroll system and calculated the overtime of employees who worked on shift hours, in addition I searched for events and contacted resort and hotels for survey purposes. Other than that, I made filings about employee medical claims and various other work related to human resources. In every company, they will have SWOT Analysis which it is one of the ways where the company can derive towards growth in order for them to know in what should be done and what are shouldn’t. As for CSF Advisers Sdn. Bhd. which is a data centre company, there are several points of SWOT Analysis that I discovered.